Implementasi Arsitektur Hybrid CodeIgniter 4 dan Python dengan Enkripsi AES pada Sistem Smart Counseling Berbasis Web - Rina Rahmawijaya; Yopi Nugraha (Journal of Information System Research (JOSH), 2026)
Counseling services at MAN 2 Garut are still dominated by conventional approaches that limit students’ privacy, making it difficult for them to openly express emotional concerns. This study aims to design and develop a web-based Smart Counseling system that supports counseling services in a safer, more responsive, and structured manner through a hybrid architecture. The development method used is Agile Scrum with the integration of the CodeIgniter 4 framework as the user interface and a Python backend as a microservice for data security. The system applies the Advanced Encryption Standard (AES) 256-bit algorithm to secure message data and a chatbot feature based on rule-based Natural Language Processing (NLP) to provide initial responses to users. Functional testing using the Black Box method on 11 scenarios showed that all main features worked as expected, including user authentication, mood tracking, counseling scheduling, chat encryption, two-way communication between students and the school counselor, and user account management by the admin. The results indicate that the developed system can support counseling services that are more inclusive, secure, and accessible for students. The main contribution of this study is integrating AES-based data security, mood-tracking emotion monitoring, and hybrid architecture into a single unified Smart Counseling system.